Qualidade, compostos bioativos e conservação da pitaia (Hylocereus polyrhizus) no semiárido brasileiro - Sarmento, José Darcio Abrantes (2017)
The aim of this work was to evaluate the quality, antioxidant potential and the conservation of the dragon fruit (Hylocereus polyrhizus), produced in the Brazilian semi-arid region, Vale do Jaguaribe-CE, Brazil, and submitted to refrigerated storage (10 ± 1 °C and 95 ±5% RH) and at room temperature (25 ± 1 °C and 45 ± 5% RH). Three experiments were realized. In the first experiment a, physical, chemical and nutritional characterization of the dragon fruit was performed, in which 12 replicates of two fruits were used, totalizing 24 fruits. In the second experiment, the conservation potential and the bioactive compounds of the dragon fruit subjected to refrigerated storage (10 ± 1°C and 95 ± 5% RH) were evaluated, where it was conducted in a completely randomized design (DIC), constituting the treatments by the evaluation times (harvest time - 0, 7, 14, 22 and 32 days), with four replicates of two fruits each. In the third experiment, the post-harvest shelf life and the bioactive compounds of the dragon fruit were submitted to storage at room temperature (25 ± 1°C and 45 ± 5% RH), where it was conducted in DIC, constituting the treatments by the evaluation times (0, 5, 8, 11 and 14 days), with four replicates of two fruits each. The fruits were harvested fully matured and transported to the Post-Harvest Physiology Laboratory of the Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN, where they were selected, installed the experiments and submitted to physical, physical-chemical, bioactive compounds and antioxidant activity (ABTS) analyzes. For the first experiment, it is concluded that the dragon fruit produced in the Brazilian semi-arid region has a high yield of pulp (71.2%), firmness (51.45 N), soluble solids (13.18 °Brix), SS/AT ratio (33.4), total sugars (7.94%) and reducing sugars (7.56%); low acidity (0.40 mg/100 g); besides significant content of minerals, emphasizing the manganese (1.95 g/kg), calcium (1.33 g/kg), potassium (1.58 g/kg) and iron (173.0 mg/kg), and the bioactive compounds betacyanin (82.27 mg/100 g) and betaxanthines (113.15 mg/100g), which makes the dragon fruit to be considered a nutrient rich fruit beneficial to health. For the second experiment, it was concluded that the dragon fruit maintained a good appearance, high sugar content and higher SS/AT ratio at the end of the storage, and it could be marketed for up to 32 days under refrigeration, without loss of quality; at which time it also obtained high firmness of the fruit and pulp, and considered content of betacyanins (58.00 mg/100 g) and betaxanthines (91.97 mg/100 g). For the third experiment, it was concluded that dragon fruit can be marketed for up to 12 days at room temperature, with no loss of quality, at which point it has a high SS/AT ratio, which is linked to pulp yield and fruit firmness, which favors consumption in natura; dragon fruit is a good source of betacyanins and its antioxidant activity is correlated with polyphenols and betacyanins